2017
DOI: 10.1016/j.tjog.2017.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Does exist a correlation between endometriosis and thrombophilic disorders? A pilot study

Abstract: Our preliminary data do not show any association between thrombophilic condition and endometriosis. Before assuming hormonal therapies, a thrombophilic plasmatic screening seems to be unnecessary in patients affected by endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…It might reflect the changes in coagulation status that has been described in patients with endometriosis [42]. Recent evidences in fact have reported higher prevalence of trombophilic disorders in endometriosis patients [43]. The lower levels of prothrombin in urines of endometriosis patients might reflect this specific coagulation status.…”
Section: Discussionmentioning
confidence: 89%
“…It might reflect the changes in coagulation status that has been described in patients with endometriosis [42]. Recent evidences in fact have reported higher prevalence of trombophilic disorders in endometriosis patients [43]. The lower levels of prothrombin in urines of endometriosis patients might reflect this specific coagulation status.…”
Section: Discussionmentioning
confidence: 89%
“…In a small study, screening for thrombophilia showed that the prevalence of prothrombin G20210A mutation and hyperhomocysteinemia in patients with endometriosis was not different from that of the general population and prevalence of factor V-Leiden mutation, was found with a lower prevalence 14 . In another study in which emphasis was given in fibrinolysis and plasminogen activator inhibitor-1 (PAI-1) gene, endometriosis was more likely in patients with 4G/5G or 4G/4G which are associated with hypofibrinolysis compared with 5G/5G PAI-1 genotype 15 .Nevertheless, the existence of 4G allele alone does not represent an independent high risk factor of thromboembolic disease.…”
Section: Genes Of Thrombotic Riskmentioning
confidence: 93%